FACTORS RELATED TO NEGATIVE STIGMA FOR HIV/ AIDS PATIENTS IN BORO-BORO VILLAGE, RANOMEETO SUB-DISTRICT SOUTH KONAWE REGENCY: Negative Stigma for HIV/AIDS Patients - Rachmawati, Umi; Firman; Pipit, Wa Ode (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2020)
Background: The high number of people living with HIV / AIDS until 2018 has created a negative stigma for HIV / AIDS patients in Boro-Boro Village, Ranomeeto Sub-District, South Konawe Regency. The purpose of this study was to determine the factors associated with negative stigma for HIV / AIDS patients in Boro-Boro Village, Ranomeeto District, South Konawe Regency Methods: Type of research is quantitative method with a cross-sectional design with a population of 585 people. Sampling technique usedd accidental sampling technique with a sample size of 83 respondents. Analysis data used the chi square test. The independent variable in this study was knowledge about HIV / AIDS, perception, and education, while the dependent variable was negative stigma for people with HIV / AIDS. The instrument of this study is a questionnaire. Result: The results showed that there was still a high negative stigma for people with HIV / AIDS with n = 69 (83.1%). There is a weak relationship between knowledge and negative stigma for people with HIV / AIDS with a value of X2 count 4.110, 0.255. There is a weak correlation between perceptions and negative stigma for people with HIV / AIDS with a value of X2 count 7.338, ? 0.331. There is a weak relationship between education and a negative stigma for people with HIV / AIDS with a value of X2count 5.551, ? 0.291. Conclusion: Researchers suggest to Ranomeeto Primary Health Care to conduct more frequent health education about HIV / AIDS and form village cadres by providing accurate knowledge about HIV / AIDS, for further researchers to add and look for variables that are closely related to negative stigma for people with HIV / AIDS in the community.